A vanishing landscape : archaeological investigations at Blakeney Eye, Norfolk - Field, Naomi (Archaeopress Archaeology, 2021)
This volume presents a report on the archaeological excavation of a small building on the Norfolk coast, locally known as 'Blakeney Chapel', in advance of expected coastal erosion at Blakeney Eye. The investigations produced evidence for multi-period occupation, with abandonments driven by the ever-changing climate.